Utilization of plant resources among the Kankanaeys in Kibungan, Benguet Province, Philippines - ABIGAIL T. BERSAMIN; JUDE L. TAYABEN; KRYSSA D. BALANGCOD; ASHLYN KIM D. BALANGCOD; AMELIA C. CENDANA; ELIZABETH T. DOM-OGEN; LANCE OLIVER C. LICNACHAN; BRENILYN SIADTO; FREDA M. WONG; Teodora D. Balangcod (Society for Indonesian Biodiversity, 2021)
Abstract. Bersamin AT, Tayaben JL, Balangcod KD, Balangcod AKD, Cendana AC, Dom-Ogen ET, Licnachan LOC, Siadto B, Wong FM, Balangcod TD. 2021. Utilization of plant resources among the Kankanaeys in Kibungan, Benguet Province, Philippines. Asian J Ethnobiol 4: 362-372. The use of plant resources for human basic need dates back to ancient times. Plants have been man’s recourse for natural healing, food, and for cultural practices. This study aimed to document the rich flora of Kibungan, Benguet that the Kankanaey tribe utilizes. Interviews and focused group discussions were used to gather data and it was supplemented with ocular inspection of the locality. Results revealed that there were various uses of plants that could be categorized into medicinal, food, house construction, and others. The leaves of medicinal plants are more frequently used to treat wounds, diarrhea, cough, and skin inflammation. Decoctions for natural remedies include gipas (Sarcandra glabra), gawed (Piper betle), and kutsay (Allium odorum). Plant foods such as fruits, root crops, and vegetables are either cultivated or gathered from the forest. Specifically, plants collected from the wild included pinit (Rubus fraxinifolius), amti (Solanum nigrum), bayabas (Psidium guajava), gatgattang (Sonchus arvensis), galyang (Alocasia macrorrhizos), and pako (Diplazium esculentum), while kamote (Ipomea batatas) and corn (Zea mays) are cultivated. The pine tree (Pinus kesiya) is the main raw material for house construction. Interestingly, dengaw (Acorus calamus) is regarded as an amulet, which is believed to ward off evil spirits.